Implementation of Internet-Based Learning System with Utilizing the Web Enhanced Course Model to Enhance Students’ Learning Motivation - Sagiman; Sahono , Bambang; Danim, Sudarwan (Corolla International Conference, 2023)
The progress of science and technology in recent times has advanced rapidly. Technology has become a necessity in human life, in line with the changing civilization of human existence itself. Various types of technology that we encounter in our daily lives, one of them is the phenomenal information and communication technology (ICT). Various types of information and communication technology devices such as computers, laptops, Android smartphones, notebooks, multimedia tools, and so on. ICT tools can be utilized to assist human work in several fields, including serving as aids in the learning process in schools and other educational institutions. This study aims to implement an internet-based learning system using the web augmented course model in order to boost students’ learning motivation. The research method employed is applied research (CAR). The subjects of this study are third-semester students of the Islamic Religious Education (PAI) program at IAIN Curup. Based on the research findings, the internet-based learning system utilizing the web augmented course model can boost students’ learning motivation. This can be observed through the results of data observation and questionnaires conducted at each stage of the cycle. The average results of the observation and questionnaire in the initial stage were 55.21 (low category), there was an increase after the first cycle to 64.54 (medium category), and further increased after the second cycle to 86.5 (high category).